Who has the power to define the ideal teacher? Insights into the social structure of Finnish teacher education - Fornaciari, Aleksi; Juutilainen, Maaret (Frontiers in Education, 2023)
In Finland, graduating teachers are expected to become 'transformational agents' who are able to critically reflect upon and evaluate what types of changes are necessary in education and who can also implement the required changes. However, based on previous studies, teacher education seems to have little influence on future teachers' core perceptions of teacher's work.Instead, previous studies have demonstrated that new teachers' perceptions might draw on tradition and cultural-historical phases of the Finnish teacher profession, and normative ideas concerning the ideal characteristics of a 'good' teacher or student teacher.In this study, we examine how student teachers' perceptions of teacherhood build upon and who has the power to define the 'ideal teacher'. Based on our study, we suggest that to understand how the perception of the ideal teacher is formed and how teacher education could better influence the transformation of these perceptions, we must consider the unofficial power relations among student teachers. These power relations seem to originate from the hegemonic discourse of the 'typical student teacher', which contains and renews traditional perceptions of teaching and teachers as authorities and experts transmitting subject content knowledge and skills to pupils. This discourse seems to be renewed among student teachers and has more impact on students' perceptions than the official aims of teacher education. Hence, in our study, the unspoken sociocultural power relations come to light in different ways, in the peer relations between student teachers but also in the students' conceptions of the teacher educators. We suggest that by unravelling the unofficial power relations in the sociocultural context of teacher education and by focusing on supporting every student teacher's agency and critical reflection, it is possible to transform the perceptions about the ideal teacher.